A construction and inspection technology of power emergency communication system based on Beidou. Issue 1 (1st December 2022) - Han, Ke; Zhang, Yifu; Wang, Yong
Abstract: In order to improve the real-time performance of information transmission of power emergency communication system, the construction and inspection technology of power emergency communication system based on Beidou is proposed in this paper. Firstly, the differences between heterogeneous networks are described based on Beidou short message. Then, the fusion probability of heterogeneous network is calculated, and the optimal communication channel is obtained. Next, communication channel link is established, and the maximum transmission range is described. In addition, the network capacity is calculated, the congestion avoidance model is established, the bandwidth is obtained by defining the interference index of the information transmission channel, the total load during the construction and inspection process is calculated, and the construction and inspection of the power emergency communication system are realized.. Experimental results show that the proposed technology has better performance in information utilization, network throughput and system response time.